Honey bee (Apis mellifera L.) broods: composition, technology and gastronomic applicability - Guiné, Raquel P.F. (2022)
Honey bee broods (larvae and pupae) can be consumed as human food, offering a rich nutritional value. Therefore, the objective of this work was to present an overview of the nutritional value of the honey bee brood and its gastronomic potential. The results indicated that honey bee broods are rich in protein (including essential amino acids), fat (essentially saturated and monounsaturated fatty acids), carbohydrates, vitamin C and those of the B complex, and minerals such as potassium, magnesium, calcium, and phosphorous. The results further highlight some variability according to the stage of development, with increasing content of fat and protein and decreasing carbohydrates from the larval to the pupal stages. The production of the honey bee brood in the hive, as well as its removal, can impact the wellbeing of the hive. This limits the production potential of the brood aimed at application for gastronomic purposes. The consumption and purchase of honey bee broods as food may be accessible in specialised markets where, for example, ethnic communities consume this type of food. However, in some markets, insects or products produced from insects are not readily accepted because of neophobia and disgust. The role of culinary chefs allied to traditional ways of preparing culinary dishes that include honey bee broods are relevant to motivate more people in western societies to consume of these types of food products.